An Implementation on Professional Competence of Junior High School English Teachers - Sari, Dewi Kartika; Muhayyang, Maemuna; Abduh, Amirullah (Har Press Indonesia, 2022)
This research aimed to find out the way junior high school English teachers implemented their professional competencies in online teaching and learning. This research applied mix method by combining quantitative and qualitative method. The data were collected from three junior high school English teachers in Makassar using questionnaire and interview. The result of this research showed that the three teachers implemented almost all the elaboration of the implementation of professional competency in which teacher A and C were in excellent category while teacher B in good category. In conclusion, junior high school English teachers in Makassar continued to apply the principles of professional competencies even though the teaching and learning process was carried out online.